Dietary L-Arginine Supplementation Affects the Skeletal Longissimus Muscle Proteome in Finishing Pigs - Ma, Xianyong (PLoS One, 2015)
Forty-eight Duroc x Landrace x Large White gilts were used to determine the relationship between proteome changes of longissimus muscle and intramuscular fat (IMF) content in arginine-supplemented pigs. Beginning at 60 kg BW, pigs were fed a corn- and soybean meal-based diet supplemented or not with 1% L-arginine until they reached a BW of 100 kg. Supplementation with 1% L-arginine did not affect the growth performance or carcass traits, while it increased IMF content by 32% (P < 0.01), it also decreased the drip loss at 48 h post-mortem and the b* meat color value at 24 h post-mortem; supplementation with 1% dietary L-arginine did not change the proportion of SFA and MUFA in muscle lipids. The proteome changes in longissimus muscle between the control and supplemented pigs showed that L-arginine significantly influenced the abundance of proteins related to energy metabolism, fiber type and structure. The increase in IMF content was positively correlated with the increased abundance of slow twitch troponin I (TNNI1) protein and negatively correlated with myosin heavy chain IIb (MyHC IIb) protein content. It is suggested that the proteome changes in longissimus muscle contributed to the greater IMF content in L-arginine supplemented pigs.